A randomized control hands-on defibrillation study—Barrier use evaluation. (June 2016) - Wampler, David; Kharod, Chetan; Bolleter, Scotty; Burkett, Alison; Gabehart, Caitlin; Manifold, Craig
Abstract: Introduction: Chest compressions and defibrillation are the only therapies proven to increase survival in cardiac arrest. Historically, rescuers must remove hands to shock, thereby interrupting chest compressions. This hands-off time results in a zero blood flow state. Pauses have been associated with poorer neurological recovery. Methods: This was a blinded randomized control cadaver study evaluating the detection of defibrillation during manual chest compressions. An active defibrillator was connected to the cadaver in the sternum-apex configuration. The sham defibrillator was not connected to the cadaver. Subjects performed chest compressions using 6 barrier types: barehand, single and double layer nitrile gloves, firefighter gloves, neoprene pad, and a manual chest compression/decompression device. Randomized defibrillations (10 per barrier type) were delivered at 30 joules (J) for bare hand and 360 J for all other barriers. After each shock, the subject indicated degree of sensation on a VAS scale. Results: Ten subjects participated. All subjects detected 30j shocks during barehand compressions, with only 1 undetected real shock. All barriers combined totaled 500 shocks delivered. Five (1%) active shocks were detected, 1(0.2%) single layer of Nitrile, 3(0.6%) with double layer nitrile, and 1(0.2%) with the neoprene barrier. One sham shock was reported with the single layer nitrile glove. No shocks were detected with fire gloves or compression decompression device. All shocks detected barely perceptible (0.25(±0.05) cm on 10 cm VAS scale). Conclusions: Nitrile gloves and neoprene pad prevent (99%) responder's detection of defibrillation of a cadaver. Fire gloves and compression decompression device prevented detection.